Dracula - Stoker, Bram (Nxb. Đồng Nai, 2009)
A true masterwork of storytelling, Dracula has transcended generation, language, and culture to become one of the most popular novels ever written. It is a quintessential tale of suspense and horror, boasting one of the most terrifying characters ever born in literature: Count Dracula, a tragic, night-dwelling specter who feeds upon the blood of the living, and whose diabolical passions prey upon the innocent, the helpless, and the beautiful. But Dracula also stands as a bleak allegorical saga of an eternally cursed being whose nocturnal atrocities reflect the dark underside of the supremely moralistic age in which it was originally written -- and the corrupt desires that continue to plague the modern human condition.